2017
DOI: 10.1007/s13238-017-0384-8
|View full text |Cite
|
Sign up to set email alerts
|

Effective and persistent antitumor activity of HER2-directed CAR-T cells against gastric cancer cells in vitro and xenotransplanted tumors in vivo

Abstract: Human epidermal growth factor receptor 2 (HER2) proteins are overexpressed in a high proportion of gastric cancer (GC) cases and affect the maintenance of cancer stem cell (CSC) subpopulations, which are used as targets for the clinical treatment of patients with HER2-positive GC. Despite improvements in survival, numerous HER2-positive patients fail treatment with trastuzumab, highlighting the need for more effective therapies. In this study, we generated a novel type of genetically modified human T cells, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 41 publications
0
51
0
Order By: Relevance
“…HER2 has been targeted with 2nd and 3rd generation CAR T cells in breast cancer [ 35 , 36 ], gastric cancer [ 37 ], glioblastoma [ 38 ], sarcoma [ 39 ], ovarian cancer [ 40 ], and osteosarcoma [ 41 ].The majority of studies have clearly demonstrated that the incorporation of co-stimulation molecules, such as CD28, 4-1BB, OX-40, ICOS, or CD27 [ 30 , 36 , 42 44 ] into CAR constructs offers better therapeutic benefit in preclinical and clinical settings. In one of these studies, Zhao et al [ 36 ] found decreased transgene expression and increased apoptotic/dead cells of Herceptin-based 4D5 HER2 CARs with or without CD28 costimulation moiety.…”
Section: Introductionmentioning
confidence: 99%
“…HER2 has been targeted with 2nd and 3rd generation CAR T cells in breast cancer [ 35 , 36 ], gastric cancer [ 37 ], glioblastoma [ 38 ], sarcoma [ 39 ], ovarian cancer [ 40 ], and osteosarcoma [ 41 ].The majority of studies have clearly demonstrated that the incorporation of co-stimulation molecules, such as CD28, 4-1BB, OX-40, ICOS, or CD27 [ 30 , 36 , 42 44 ] into CAR constructs offers better therapeutic benefit in preclinical and clinical settings. In one of these studies, Zhao et al [ 36 ] found decreased transgene expression and increased apoptotic/dead cells of Herceptin-based 4D5 HER2 CARs with or without CD28 costimulation moiety.…”
Section: Introductionmentioning
confidence: 99%
“…Animal models have been extensively used to study the pathogenesis and metastatic mechanisms of gastric cancer and play an extremely important role in the evaluation of the efficacy and toxicity of therapeutic drugs [8][9][10]. At present, gastric cancer animal models mainly include the following: the induction model, the transplantation model, and the genetic engineering model [11].…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity of iKP-19 CAR-T cells or CD19-CAR-T cells against Daudi cells or normal B cells was evaluated by using a standard lactic dehydrogenase (LDH) release assay (Promega, Madison, WI, USA) as described earlier by Song et al [ 50 ]. Briefly, target cells were seeded at a density of 10 4 cells per well in 96 well plate in a triplicate manner.…”
Section: Methodsmentioning
confidence: 99%